Pembatasan Usia Pertanggungjawaban Pidana Anak dalam Peraturan Perundang-Undangan - Satya Prema, I Ketut Arjuna; Ruba'i, Masruchin; Aprilianda, Nurini (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This article aims to discuss the age of criminal responsibility of children according to statutory regulations in Indonesia and the legis ratio of determining the age of child responsibility according to Law Number 11 of 2012 concerning the Criminal Justice System for Children. The study uses normative legal research with a statutory approach. The results of the study show that three regulations are governing the age limit for a child to be held criminally responsible, namely the Criminal Code Act, Law Number 3 of 1997 concerning Juvenile Court, Law Number 11 of 2011 concerning the Criminal Justice System for Children. These three regulations differ in determining the minimum limit for a child to be held liable for criminal liability. Psychological, sociological, and pedagogical aspects are the base for the ratio of the legal determination of the minimum age of 12 years in the Criminal Justice System for Children.